2019
DOI: 10.1039/c8ra10540e
|View full text |Cite
|
Sign up to set email alerts
|

Novel triangular silver nanoparticle modified membranes for enhanced antifouling performance

Abstract: This study marks the first ever attempt at the successful fabrication of a novel reactive membrane to combat fouling through layer-by-layer (LBL) surface modification with polyelectrolyte (PE), followed by anisotropic triangular silver nanoparticles (TSNP). The morphology and the presence of TSNP on the membrane was confirmed by HR-TEM, FE-SEM and XPS. The charge density of the novel membrane (PE-TSNP) was increased 15.6 fold, as a result of the sharp-tip morphology of the TSNP forming tip-based "hot spots" on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The modified membrane also poses an enhanced flux of 36% and high flux recovery of up to 96%. Moreover, the modification with silver nanoparticles with a triangle shape gives long-term membrane stability for up to 4 months of usage [43].…”
Section: Colloidal Silver Nanoparticle-reinforced Membranementioning
confidence: 99%
“…The modified membrane also poses an enhanced flux of 36% and high flux recovery of up to 96%. Moreover, the modification with silver nanoparticles with a triangle shape gives long-term membrane stability for up to 4 months of usage [43].…”
Section: Colloidal Silver Nanoparticle-reinforced Membranementioning
confidence: 99%
“…Furthermore, the SEM image of the surface of the virgin membrane showed the presence of rod-shaped bacteria ( Figure 12 a), which were not observed on the AgPNP embedded membrane surface. The visible particles ( Figure 12 b) on the modified membrane resembled the immobilized AgPNPs that are shown in Figure 4 c. This clearly demonstrates that the PAH/PAA BL assisted AgPNP immobilization imparted the antimicrobial property to the UF membrane, implying less activity [ 76 ] and attachment of microorganisms that initiate the multi-step process of biofilm formation on the membrane surface [ 77 ]. A previous study by Liu et al [ 78 ], who tested a Ag-loaded chitosan/cellulose acetate blended membrane, suggested that functionalizing an anti-adhesive membrane surface with anti-microbial property was an effective way of providing anti-biofouling performance when compared to the approach of killing/inactivating the bacteria after attachment to the membrane surface.…”
Section: Resultsmentioning
confidence: 93%
“…Hence, the interaction forces between the modified membrane and the ALG+BSA+TA complex are weaker than those between the pristine membrane and the cake layer. This can be explained by the more pronounced hydrophilic properties and the lower roughness of the membranes containing nanoparticles [39,40]. The similar performance of the two membranes after the increased cross-flow velocity cleaning strategy can be explained by the fact that the shear stress generated by a 6 cm/s cross-flow velocity was sufficiently high to break the bonds between the ALG+BSA+TA complex and pristine/modified membrane.…”
Section: Discussionmentioning
confidence: 93%